2019
DOI: 10.1111/epi.16329
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of genetic predisposition to develop acquired epileptogenesis: The FAST and SLOW rats

Abstract: Epidemiological data and gene association studies suggest a genetic predisposition to developing epilepsy after an acquired brain insult, such as traumatic brain injury. An improved understanding of genetic determinants of vulnerability is imperative for early disease diagnosis and prognosis prediction, with flow‐on benefits for the development of targeted antiepileptogenic treatments as well as optimal clinical trial design. In the laboratory, one approach to investigate why some individuals are more vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
(292 reference statements)
0
2
0
Order By: Relevance
“…Genetic strains of rats that kindle fast or slow have been developed by selective breeding to assess genetic predispositional contributions to acquiring epilepsy and reactivity to uncertainty and threat ( McIntyre et al, 2002 ; McIntyre and Gilby, 2007 ; Leung et al, 2019 ). Initial afterdischarge thresholds are not different between fast and slow kindling rats but fast kindling rats develop generalized motor seizures about 4 times as fast as slow kindling rats ( Racine et al, 1999 ).…”
Section: Genetic Influences On Hyperexcitabilitymentioning
confidence: 99%
“…Genetic strains of rats that kindle fast or slow have been developed by selective breeding to assess genetic predispositional contributions to acquiring epilepsy and reactivity to uncertainty and threat ( McIntyre et al, 2002 ; McIntyre and Gilby, 2007 ; Leung et al, 2019 ). Initial afterdischarge thresholds are not different between fast and slow kindling rats but fast kindling rats develop generalized motor seizures about 4 times as fast as slow kindling rats ( Racine et al, 1999 ).…”
Section: Genetic Influences On Hyperexcitabilitymentioning
confidence: 99%
“…Similarly, in a population-based cohort study of more than 1.6 million Danish adults and children, a family history of epilepsy was associated with an approximately 10-fold higher risk of developing late-onset seizures following a severe brain injury (Christensen et al, 2009). Limited studies to date have specifically probed for gene associations with acquired epilepsy risk, as recently reviewed (Leung et al, 2019). Consistent with the abovementioned evidence on IL-1b polymorphisms and PTE risk, a meta-analysis found that specific alleles of both IL-1b and IL-1a have also been associated with risk of epilepsy after FS (Saghazadeh et al, 2014).…”
Section: Early Life Neurotraumamentioning
confidence: 99%